Case report: A compound heterozygous mutations in ASNS broadens the spectrum of asparagine synthetase deficiency in the prenatal diagnosis - Zhu, Linyan; Sun, Yixi; Xu, Yuqing; Jin, Pengzhen; Ding, Huiqing; Dong, Minyue (Frontiers in Pediatrics, 2023)
Asparagine synthetase deficiency (ASNSD) is a rare congenital disorder characterized by severe progressive microcephaly, global developmental delay, spastic quadriplegia, and refractory seizures. ASNSD is caused by variations of the ASNS gene. The present study showed a Chinese family with a fetus suffering microcephaly. Whole-exome sequencing and Sanger sequencing were used to identify the disease-associated genetic variants. Compound heterozygous variants c.97C>T p. (R33C) and c.1031-2_1033del were identified in the ASNS gene and the variants were inherited from the parents. The mutation site c.97C>T was highly conserved across a wide range of species and predicted to alter the local electrostatic potential. The variant c.1031-2_1033del was classified pathogenic. However, there is no case report of prenatal diagnosis of ASNSD. This is the first description of fetal compound mutations in the ASNS gene leading to ASNSD, which expanded the spectrum of ASNSD.